GAMIFICATION AS A MEANS OF IMPROVING THE EFFICIENCY OF THE LEARNING PROCESS IN SECONDARY EDUCATION - Oksana Salata; Oleksandr Trukhan (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article presents the essence and advantages of gamification and its implementation in the educational process; the use of game design elements by teachers in the educational environment. The purpose is to study and present the essence and benefits of gamification and its implementation in the educational process. To reveal the main functions of gamification as a method, the author used the method of induction and deduction, which made it possible to draw conclusions about the details of the gamification procedure and the possible results achieved in the game; the method of comparison, which helped to compare the results of using traditional teaching in lessons in a general education institution and lessons involving gamification techniques. Gamification as a tool that uses different types of student motivation is revealed. Gamification is shown as a complex of game methods and technologies aimed at developing skills and improving the learning process and quality of education. Gamification is revealed as a tool that helps teachers, regardless of the discipline they teach, to make learning interactive and engaging. The potential of using gamification methods to increase students' motivation, engagement, and performance is presented, mainly by creating a comparative learning environment that affects how students learn. It is concluded that improving students' motivation and engagement in learning activities is important for the development of skills and competencies. A teacher's understanding of how gamification methods affect student behavior can help them choose the appropriate methods for their students.